The role of values in the development and prevention of emotional burnout among employees: a theoretical review - Zhdanova, P.R. (Sovremennaâ Zarubežnaâ Psihologiâ, 2025)
Context and relevance. In the context of modern professional activity, emotional burnout is becoming an increasingly common phenomenon. It not only negatively impacts the physical and psycho-emotional well-being of employees but also reduces overall efficiency and increases staff turnover. The study of the role of personal and professional values in the development and prevention of burnout is particularly relevant. Values reflect an individual's internal beliefs and determine their attitude toward work, interactions with colleagues, and approach to fulfilling professional duties. They form the foundation of motivation, influencing what a person considers important and meaningful in their activities. Understanding the connection between values and emotional burnout is crucial both for theoretical comprehension of the problem and for developing effective burnout prevention strategies within organizations. Conclusions. Internal professional values, as personal resources, enhance employee engagement, contributing to a reduction in emotional burnout. Additionally, the alignment between personal and corporate values plays a significant role in reducing burnout by supporting psychological well-being and motivation. Контекст и актуальность. В условиях современной профессиональной деятельности эмоциональное выгорание становится все более распространенным явлением. Оно не только негативно влияет на физическое и психоэмоциональное состояние сотрудников, но также снижает общую эффективность и увеличивает текучесть кадров. Особую актуальность приобретает исследование роли личных и профессиональных ценностей в развитии и предотвращении выгорания. Ценности отражают внутренние убеждения человека и определяют его отношение к работе, взаимодействие с коллегами и подход к выполнению профессиональных обязанностей. Они формируют основу мотивации, влияя на то, что человек считает важным и значимым в своей деятельности. Изучение связи ценностей и эмоционального выгорания становится важным как для теоретического понимания проблемы, так и для разработки эффективных стратегий профилактики выгорания в организациях. Цель. Провести анализ научных публикаций и выявить, как ценности связаны с эмоциональным выгоранием на рабочем месте. Основные выводы. Внутренние профессиональные ценности как личные ресурсы повышают вовлеченность сотрудников, что способствует снижению уровня эмоционального выгорания. Также соответствие между личными и корпоративными ценностями играет значимую роль в снижении выгорания, поддерживая психологическое благополучие и мотивацию.